Peak Height Velocity (PHV) and Its Non-Significant Relationship with Physical Performance in Adolescent Soccer Athletes - Aldair Jiménez Carrillo; Jesus Leon Lozada-Medina (INSPIREE: Indonesian Sport Innovation Review, 2026)
The  purpose  of  the study. This study aimed to analyze the relationship between conditional capacities (agility, speed, aerobic capacity, and explosive strength) and somatic maturation—expressed as years from PHV—in a cohort of youth male soccer players. Materials and methods. A quantitative, correlational, and cross-sectional design was employed. Seventeen male soccer players aged 14–15 years participated. Somatic maturation was assessed via anthropometric estimation of PHV. Physical performance was evaluated using the Andersen Test (aerobic capacity), 20 m sprint (linear speed), Illinois Agility Test, and horizontal jump (explosive strength). Tests were administered under standardized conditions across three sessions. Data analysis included descriptive statistics, Pearson correlation coefficients, and ANOVA using SPSS software. Results. Descriptive findings indicated substantial variability in maturation (mean PHV = –0.89 ± 1.21 years), despite a homogenous chronological age. Correlation analyses revealed no statistically significant associations between PHV and the measured performance variables (p > .05). The strongest—but still non-significant—trend appeared between PHV and agility (Illinois test; r = –0.319), suggesting that more mature players may demonstrate slightly better change-of-direction ability. Overall, maturation did not directly predict aerobic performance, explosiveness, or speed in this sample. Conclusions. Somatic maturation, expressed through PHV, did not significantly relate to physical performance indicators among the adolescent soccer players studied. The considerable variability in maturation reinforces the need for coaches to consider biological age rather than relying solely on chronological age when interpreting performance, prescribing training loads, and making talent selection decisions. These findings highlight the importance of individualized assessment and developmentally informed training in youth soccer contexts.